Pengembangan E-Modul Perubahan Lingkungan Berbasis Problem Based Learning Pada Isu Sungai Batanghari Untuk Meningkatkan Literasi Lingkungan dan Kemampuan Berpikir Kritis Siswa - Muhammad Akbar; Suhartini Suhartini (Jayapangus Press, 2026)
Students’ low levels of environmental literacy and critical thinking skills remain a challenge in biology education. These issues are influenced by the use of teaching materials that are still largely conceptual, a teaching approach that tends to be teacher-centered, and the suboptimal use of local environmental issues as learning resources. This study aims to develop a Problem-Based Learning (PBL)-based e-module on environmental change focused on the issue of pollution in the Batanghari River that is valid, practical, and effective in improving the environmental literacy and critical thinking skills of students in Phase E. This study is a research and development (R&D) project using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The quality of the product was assessed based on the aspects of validity, practicality, and effectiveness. Data were collected through expert validation sheets, practicality questionnaires, lesson implementation sheets, environmental literacy instruments, and critical thinking ability tests. The data were analyzed using descriptive statistics, the N-Gain test, and MANOVA. The research results show that the e-module was deemed valid, with an average validation score of 3.89 from subject matter experts and 3.23 from media experts. The product’s practicality received an average score of 3.72 from teachers and 3.60 from students, with 100% implementation of the learning activities. The average N-Gain for environmental literacy in the experimental class was 57.28% and 30.17% in the control class, while the N-Gain for critical thinking skills was 76.58% and 45.53%, respectively. The MANOVA results showed a significant difference between the experimental and control classes (p < 0.001). Thus, the developed e-module is valid, highly practical, and effective for improving environmental literacy and critical thinking skills among Phase E students.